Cognitive, Social and Moral Development of Primary School Age Children in the Learning Process - Maharani, Nur Asdita; Rahma Wati, Fitri (International Journal of Students Education, 2023)
This research aims to (1) determine the cognitive development of students in the learning process, (2) to determine the moral development of students in the learning process, and (3) to determine the social status of children at elementary school age. This research uses the literature study method. As we know, development is a continuous procedure that begins in the womb until adulthood. Intellectual development is related to the cognitive abilities possessed by individuals, namely the potential for solving problems and thinking.Characteristics of the social and moral cognitive development of elementary school children are that they are aware of the social roles, religion, race and socio-economic status of their peers, accept cultural stereotypes and mature attitudes towards their status, thus giving rise to group awareness in behaving in their social environment. These characteristics will persist until late childhood and will continue until they are adults if educators provide stimulus to continue their developmental tasks maturely. This stimulus takes the form of guidance, direction, and provides a good and healthy social and cultural environment in social, cognitive and moral development so that it has implications for the formation of good social attitudes.Based on research with a literature review that the author conducted, it was found that elementary school students in the concrete operations section were aged 7-11 years. Moral development is concerned with the growth of rules and conventions that determine the appropriate way to interact with other people. Moral development is a critical aspect that requires careful attention because it is closely related to children's spiritual and social intelligence. Social development is a child's learning process in adapting to the norms, morals and traditions of a group